Research on plugging mechanism and parameter optimization of long hole blasting - Zhongchang YIN; Junsheng SONG; Wenhan WANG (Meitan kexue jishu, 2023)
The quality of deep hole blasting blocking directly affects the effective use of explosive energy and the rock breaking effect of blasting. Through a combination of theoretical analysis, laboratory model tests, numerical simulations and field tests, a study was carried out to investigate the blocking mechanism, blocking method, selection of blocking materials and blocking length of ultra-deep hole blasting, to obtain the damage effect of blast-generated gas on the surrounding rock and the range of fracture generation under the complete blocking effect, and to select the blocking method and blocking parameters to improve the blocking quality of the blast hole. In the study of the plugging mechanism of the shell hole, a reasonable minimum plugging length was derived through theoretical analysis. In the laboratory model test, the physical and mechanical parameters such as cohesion and internal friction angle of the gun clay were obtained through the direct shear test of the gun clay. The LS-DYNA software was applied to simulate the blasting model with or without blocking, and the rock body near the free surface was subjected to greater stress than that with blocking. This shows that the combined effect of blast stress waves and detonation gas can improve the efficiency of explosive breakage in the presence of clay blocking. The PFC software analyses the movement law of the gun clay for different blocking lengths, and obtains that a reasonable gun clay length is the main factor to ensure that the blast gas acts and does not produce external damage, and verifies the theoretical calculation method of the shortest gun clay blocking length, while the field test results further confirm the reasonableness of the effective blocking length.